Participation in voting over budget allocations: A field experiment - Clemens Puppe; Jana Rollmann (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2022)
We study the effect on the participation rate of employing different voting rules in the context of the problem to allocate a fixed monetary budget to two different public projects. Specifically, we compare the mean rule according to which the average of the individually proposed allocations is implemented with the median rule which chooses the allocation proposed by the median voter as the social outcome. We report the results of a field experiment in which subjects (students of KIT) could allocate money to fund two different public projects, the student's bike shop and a campus garden project. The treatment variable was the collective decision rule employed. While the mean and median rules have very different properties in theory, we found no significant treatment effect on the participation rate. Our results nevertheless shed important light on the use of different voting rules in the context of budget allocation in practice.
Keywords: 330